304 스테인리스강 용접 열영향부의 입계 부식에 미치는 탄소함량의 영향 - 오은종(Eun-Jong Oh); 이재형(Jae-Hyung Lee); 조성우(Sung-Woo Cho); 이원근(Won-Geun Yi); 남기우(Ki-Woo Nam) (대한용접·접합학회지, 2019)
304 stainless steels with carbon contents of 0.074wt%C and 0.064wt%C were tested to investigate the effect of carbon content on intergranular corrosion in the heat affected zone. Stainless steels with two types of carbon content were subjected to various tests to identify characteristics such as nondestructive properties, mechanical properties, chemical composition, delta ferrite content, and structural observation. In the ASTM A262 test for detecting the intergranular attack associated with chromium carbide precipitates, 304 stainless steel with a carbon content of 0.064wt%C was found to be resistant to intergranular corrosion, but 304 stainless steel with a high carbon content of 0.074wt%C was found to have intergranular corrosion in the heat affected zone 2 to 3 mm away from the fusion line. Using temperature distribution analysis it was confirmed that the 2 to 3 mm point at the fusion line persists for approximately 3 to 6 seconds at the sensitivity temperature range of 650~870℃. This result confirmed the corrosion test results of the 304 stainless steel with a high carbon content of 0.074wt%C. Therefore, the carbon content of stainless steel to be employed industrial field welding needs to be limited to a maximum 0.065wt%C in order to ensure the corrosion resistance of 304 series stainless steel in a corrosive environment. KCI Citation Count: 0